The evolution of Turkey’s diaspora engagement policies (2003-2014) - Guedes Brum, Alex (2023)
This article explain Turkey’s sudden interest in implementing diaspora engagement policies during the period in which Erdo?an was the country’s prime minister (2003-2014). It is argued that the evolution of these policies was the result of a combination of domestic, transnational and international factors: internally, the AKP’s rise to power resulted in economic and political reforms and the promotion of a new national identity based on neo-Ottomanism and the Sunni-Muslim nationalism. Transnationally, the growing socio-economic and political influence of Turkish communities in host countries has urged Turkey to reconsider the effectiveness of its diaspora as a source of influence abroad, as well as an electorate in national elections. International developments have also shaped the country’s new diasporic agenda, such as the rise in bargaining power vis-à-vis the EU since the early 2000s and the rise of Islamophobia in the post-9/11.